Exploring the Elven World: On Writing Bergrún - Sesselía Ólafsdóttir 1987- (2024)
This BA thesis is composed of two parts: a few chapters from the novel Bergrún and an exposition. The chapters come to about 17,500 words and the exposition is approximately 3,000 words. In the spring of 2023, I took a course in creative writing, taught by Dr. Beth Rebecca Cortese, and during that time I wrote the first three chapters of the novel Bergrún. For a final thesis I wanted to keep developing the story, so I continued from where I left off, and wrote the next six chapters. The novel is about Bergrún, a teenage girl who ends up in the Icelandic Elven World. She enters the underground cave system of Iceland and meets elves and other humans who, like her, agree to help the light elves defend themselves against the evil queen who resides in East Iceland. The humans who are led into the Elven World all have a specific combination of elemental powers that are useful to the elves, and during their stay they learn to hone their skills. Bergrún is a seer, which is a talent the elves desperately need to be able to predict, and defend against, the queen’s actions. The exposition details my approach to worldbuilding and the development of the physical and cultural setting, particularly regarding the reprocessing of Icelandic culture and folklore, as I feel more Icelandic fantasies should make use of the substantial material we possess in our folktales. Additionally, I explore how foreshadowing and payoff, as well as additional sensory details, play a major role in the reader‘s satisfaction.